HOW TO BUILD AN EPISTEMIC ECHO CHAMBER. - Hales, Steven (Teorema, 2025)
The present paper offers an explanatory model of the logical structure of epistemic echo chambers. Most work done so far on echo chambers attributes their cause to epistemic vice: they arise due to poor reasoning or cognitive biases. I argue that instead they are a predictable outcome of rational belief formation. They result from groups aggregating and magnifying the beliefs of their members, and the reflection of group consensus back to individuals who then increase their confidence to better conform with the group. This process is recursive, driving both individuals and epistemic groups to complete conviction. I also argue that not all echo chambers are bad. They are virtuous when they increase credence in the truth for those inside and inoculate them against the falsehoods, corrupt data, and fallacious reasoning outside the chamber. Echo chambers are bad when they start with falsehoods and amplify confidence in them.